Probabilistic transition of condition: render facades - Silva, A.; Neves, Luís C.; Gaspar, Pedro L.; de Brito, J. (Taylor & Francis, 2016)
The service life of cement-rendered facades is closely related to the environmental conditions that they are exposed to. The probability distribution is determined for the degradation condition of render facades considering different environmental exposures. A sample of 100 render facades was subjected to meticulous fieldwork to determine their condition. The analysis focuses on the environmental factors that most influence the overall degradation of the facades, evaluated through the condition level. Probabilistic models based on Markov chains are developed to predict the evolution of facade deterioration according to exposure to outdoor environmental conditions. The proposed model provides data on the synergy between the degradation agents and the degradation condition of render facades, the average time of permanence in each degradation level and indications of the effect of degradation on the durability of render that may be applied in the implementation and fine tuning of maintenance procedures. Better understanding the durability of render facades allows a more rational management of their maintenance, contributing to a reduction of their life cycle costs. The proposed stochastic model provides information that can be applied in the context of insurance policies, allowing an evaluation of the risk of failure of coatings.